A Cambrian spiny stem mollusk and the deep homology of lophotrochozoan scleritomes - Guangxu, Z; Parry, L; Vinther, J; Ma, X (American Association for the Advancement of Science, 2024)
Mollusks encompass enormous disparity, including familiar clams and snails alongside less familiar aculiferans (chitons and vermiform aplacophorans) with complex multicomponent skeletons. Paleozoic fossils trace crown mollusks to forms exhibiting a combination of biomineralized shells and sclerites (e.g., scales, spines, and spicules). We describe a shell-less, Cambrian stem mollusk, Shishania aculeata gen. et sp. nov., with conical, hollow chitinous sclerites and a smooth girdle, broad foot, and mantle cavity. The sclerites have a microstructure of narrow canals consistent with the impressions of chaetal microvilli found in annelids and brachiopods. Shishania sclerites provide a morphological stepping stone between typical chaetae (chitinous bristles) and the external organic part of aculiferan sclerites that encloses a mineralized body. This discovery reinforces a common origin of lophotrochozoan chaetae and the biomineralized aculiferan sclerites, suggesting that the mollusk ancestor was densely covered with hollow chitinous chaetae.